Coping With Stress During a Job Loss - Heidi Liss Radunovich (EDIS)
FCS-5265, a 4-page fact sheet by Heidi Liss Radunovich, describes the typical emotional reactions people have when they experience an unexpected job loss, and lists ways people can take care of themselves during the stress of a job loss. Includes references. Published by the UF Department of Family Youth and Community Sciences, August 2008.